Experimental study on geogrid-soil interface properties based on pullout tests: A case study - Zhijie Wang; Guowei Zhang; Guangqing Yang; Yan Qin; Shiguang Zhou (Case Studies in Construction Materials)
The geogrid-soil interaction, which is crucial to the safety and stability of reinforced soil structures, is determined by the key variables of both geogrids and soils. To investigate the influence of backfill and geogrid on their interface behavior of the reinforced soil retaining walls in Yichang section of Shanghai-Chongqing- Chengdu high-speed railway, a series of laboratory pullout tests were carried out considering the influence of water content and compaction degree of the backfill as well as tensile strength of the geogrid. The development and evolution law of pullout force-pullout displacement curves and interface characteristics between geogrid and soil under various testing conditions were analyzed. The results showed that with increasing water content, the geogrid pullout force decreased under the same pullout displacement. The interfacial friction angle of the geogrid-soil interface showed a slowly increasing trend with increasing water content. The variation of the interfacial friction angle ranged between 9.2° and 10.7°. The interfacial cohesion, however, decreased rapidly with increasing water content. With increasing degree of compaction, the interfacial friction angle and the interfacial cohesion of the geogrid-soil interface gradually increased. The change of the interfacial cohesion with the compaction degree was more significant. When the degree of compaction increased from 0.87 to 0.93, the interfacial cohesion increased around 7 times. The tensile strength of geogrid has certain influence on its pullout force-pullout displacement relationship. High-strength geogrid could significantly improve the mechanical properties of the geogrid-soil interface. The investigation results can provide some reference for the design and construction of geogrid reinforced soil structures.